2012
DOI: 10.1093/mnras/sts323
|View full text |Cite
|
Sign up to set email alerts
|

Basic parameters and properties of the rapidly rotating magnetic helium-strong B star HR 7355*

Abstract: The spectral and magnetic properties and variability of the B2Vnp emission-line magnetosphere star HR 7355 were analyzed. The object rotates at almost 90% of the critical value, meaning it is a magnetic star for which oblateness and gravity darkening effects cannot be ignored any longer. A detailed modeling of the photospheric parameters indicate that the star is significantly cooler than suggested by the B2 spectral type, with R eff = 17 500 K atypically cool for a star with a helium enriched surface. The spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 27 publications
9
76
0
Order By: Relevance
“…The rapid change in the strength of the mean longitudinal magnetic field by about 1 kG over 88 min in HD 345439 is reminiscent of the mean longitudinal magnetic field behaviour in the fast-rotating σ Ori E analogue HR 7355 with a rotation period of 0.52 d. This star shows a field variation of about 1 kG within a phase interval of 0.1, corresponding to 75 min (see Fig. 3 in Rivinius et al 2013). Therefore, it is possible that the rotation period of HD 345439 is also significantly shorter than one day.…”
Section: Magnetic Field Measurements Using Fors 2 Spectropolarimetrymentioning
confidence: 78%
See 1 more Smart Citation
“…The rapid change in the strength of the mean longitudinal magnetic field by about 1 kG over 88 min in HD 345439 is reminiscent of the mean longitudinal magnetic field behaviour in the fast-rotating σ Ori E analogue HR 7355 with a rotation period of 0.52 d. This star shows a field variation of about 1 kG within a phase interval of 0.1, corresponding to 75 min (see Fig. 3 in Rivinius et al 2013). Therefore, it is possible that the rotation period of HD 345439 is also significantly shorter than one day.…”
Section: Magnetic Field Measurements Using Fors 2 Spectropolarimetrymentioning
confidence: 78%
“…Groote & Hunger 1997), only two other stars, HR 5907 and HR 7355, are known to belong to this group, which is called the σ Ori E analogues (Grunhut et al 2012;Rivinius et al 2013). Their very strong magnetic fields and extraordinary fast rotation pose a mystery for theories of star formation and magnetic field evolution.…”
Section: Discussionmentioning
confidence: 99%
“…To identify and model the physical processes responsible for the generation of their magnetic fields, it is important to establish whether magnetic fields can also be detected in massive stars that are fast rotators and have runaway status. Recent detections of strong magnetic fields in very fast rotating early B-type stars indicate that the spindown timescale via magnetic braking can be much longer than the estimated age of these targets (e.g., Rivinius et al 2013). Furthermore, current studies of their kinematical status identified a number of magnetic O and Of?p stars as candidate runaway stars (e.g., Hubrig et al 2011c).…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated by several recent studies (e.g. Townsend, Owocki & Groote 2005;Bohlender & Monin 2011;Grunhut et al 2012a;Rivinius et al 2013), the LPV show specific characteristics that reflect the rigid motion of these clouds that is unique to these stars. The characteristics of these clouds (e.g.…”
Section: Magnetically Confined Winds and Magnetospheresmentioning
confidence: 72%
“…Oksala et al 2012;Grunhut et al 2012a;Rivinius et al 2013). As illustrated by several recent studies (e.g.…”
Section: Magnetically Confined Winds and Magnetospheresmentioning
confidence: 80%